2010
DOI: 10.1093/annonc/mdq013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ipilimumab monotherapy in patients with pretreated advanced melanoma: a multicenter single-arm phase II study

Abstract: Ipilimumab demonstrated clinical activity with encouraging long-term survival in a previously treated advanced melanoma population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
286
1
22

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(324 citation statements)
references
References 26 publications
15
286
1
22
Order By: Relevance
“…However, these modalities are still largely suboptimal and carry substantial immune toxic effects in the skin, gastrointestinal tract, and other syndromes such as uveitis or hypophysitis (31)(32)(33). This occurs because anti-CTLA4 and anti-PD1 target general immune checkpoints, which are not tumor-specific, although those caused by anti-PD1 seem to be milder (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, these modalities are still largely suboptimal and carry substantial immune toxic effects in the skin, gastrointestinal tract, and other syndromes such as uveitis or hypophysitis (31)(32)(33). This occurs because anti-CTLA4 and anti-PD1 target general immune checkpoints, which are not tumor-specific, although those caused by anti-PD1 seem to be milder (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Rare targets for autoimmunity include the joints and kidneys [14]. In Phase II studies less than 1 in 100 treated patients developed Grade 3 or 4 cough, dyspnea or pleural effusion [15]. There is only one previous report of autoimmune pulmonary toxicity related to ipilimumab administration [16].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with unresectable Stage III or IV melanoma, administration of ipilimumab resulted in a 47.2% 1-year survival rate. 56 A long-term follow-up of 177 patients with metastatic melanoma treated with ipilimumab revealed an 88-month median duration of objective response, which suggests that complete remission is possible in some patients. 65 Additionally, Weber et al demonstrated that ipilimumab is considered safe for patients with metastatic melanoma in whom there was CNS involvement.…”
Section: Cytotoxic T-lymphocyte Antigen-4 Blockade With Ipilimumabmentioning
confidence: 99%